COMPLEMENTARY ACCOUNTING THROUGH THE GENERAL LEDGER. - Mautner, Oscar; Mauriello, Joseph A. (The Accounting Review, 1953)
The article highlights that books of original entry, in the form of journals, express the two-fold effect of each transaction through debit and credit accounts presented as complementaries. The books of final entry, in the form of ledgers, then divorce the complementary elements by classifying the debits and credits by account titles as separate units. However, considerable benefit can be derived by management and auditors if the complementary elements set forth in the journals are retained in the ledger. This objective is accomplished simply by changing the ruling of the accounts in the general ledger. The single debit and credit columns currently in use will be replaced by a series of debit and credit columns to accommodate each related complementary account. The columns on the debit side will show the credit complementary accounts common to the account in question. The columns on the credit side will show the related debit complementary accounts. Since the number of complementary accounts pertaining to a particular account vane, two sizes of account sheets can be used. A single page-spread will suffice for accounts with few complementaries. A two-page-spread will be used for accounts with numerous complementaries.